Modulation instability analysis and optical solutions of an extended (2+1)-dimensional perturbed nonlinear Schrodinger equation - Ali, Karmina K.; Tarla, Sibel; Ali, Mohamed R.; Yusuf, Abdullahi (Elsevier, 2023)
We examine an extended (2+1)-dimensional perturbed nonlinear Schrodinger equation with Kerr law nonlinearity in a nano-optical fiber with fourth-order spatial derivatives in this paper. We develop various optical solutions to the equation under study using the Jacobi elliptic expansion method. We investigate the consequences of nonlinearity and spatial dispersion in spatial directions x and y. Furthermore, by investigating the stability condition of this nonlinear equation, we derive the linear stability analysis. The innovative evolutionary behaviors in the 3-dimensional profile are provided under constraint circumstances to indicate the wave propagation direction.
Keywords: Perturbed nonlinear Schrodinger equation; Jacobi elliptic function expansion technique; Stability analysis